Professional satisfaction in the hospital context and the humanized performance of clown doctors (Research, Society and Development, 2022)
Humanization is a set of principles that aims to add to health care, playful therapies and laughter therapy help in care, as it allows the patient to forget about hospitalization for a few moments. Clown therapy appears in order to complete health care, reducing the physical and emotional exhaustion of patients, also intervening in the humanization of companions, patient family members and hospital professionals. This study aimed to evaluate the perception of health professionals regarding the performance of Clowns of Purpose and the professional satisfaction of the multidisciplinary team. The research was carried out through two forms, using a qualitative and quantitative approach in which, from the perception of 40 professionals from different categories, the professional satisfaction and performance of Clowns of Purpose in two hospitals in Aracaju/SE were evaluated. The dissatisfaction items found were salary, overwork, equity and progression, while the job satisfaction items were the nature of work and responsibility. The professionals obtained a general average of 4.47 if they were satisfied according to the global score of the Professional Satisfaction Scale. It was found that 92.5% of professionals perceive the performance of clowns as beneficial in several points (transformation of the environment, professionals' mood and improvement of the general situation of patients). It is concluded that workers in general are satisfied professionally and most of them are consistent with the presence of the group in the hospital, understanding its importance.